Do Extratropical Cyclones Impact Synoptic‐Scale Variability of the Arctic Oscillation During Cold Season? - Shengyi Qian; Haibo Hu; Kevin I. Hodges; Xiu‐Qun Yang (Geophysical Research Letters, 2025)
Abstract The Arctic Oscillation (AO) is the most significant mode of sea level pressure (SLP) anomalies in the Northern Hemisphere, exhibiting significant multiple‐timescale variability from synoptic to decadal. Using NCEP Climate Forecast System Reanalysis data from 1979 to 2022 during the cold season (November–April), this study identifies the relationship between the number of extra‐tropical cyclones entering and exiting the Arctic and the AO synoptic variability. The Joint Net Cyclone Flux (JNCF) is significantly correlated with the spatio‐temporal evolution of the synoptic AO and the composites of SLP associated with the JNCF produce AO‐like patterns. Subsequent piecewise potential vorticity inversion reveals the impacts of extratropical cyclones on the synoptic‐scale AO‐like geopotential height anomalies at different altitudes. The effects of extratropical cyclones are more important than Arctic stratospheric PV intrusions. Furthermore, the upper‐level dynamic processes among all extratropical cyclone effects dominate the evolution of synoptic‐scale AO‐like geopotential height anomalies.